Coherent Control of the Nonlinear Emission of Single Plasmonic Nanoantennas by Dual‐Beam Pumping. Issue 20 (5th August 2022) - Di Francescantonio, Agostino; Locatelli, Andrea; Wu, Xiaofei; Zilli, Attilio; Feichtner, Thorsten; Biagioni, Paolo; Duò, Lamberto; Rocco, Davide; De Angelis, Costantino; Celebrano, Michele; Hecht, Bert; Finazzi, Marco
Abstract: The control of nonlinear optical signals in nanostructured systems is pivotal to develop functional devices suitable for integration in optical platforms. A possible control mechanism is exploiting coherent interactions between different nonlinear optical processes. Here, this concept is implemented by taking advantage of the strong field enhancement and high optical nonlinearity provided by plasmonic nanostructures. Two beams, one at the angular frequency ω, corresponding to the telecom wavelength λ = 1551 nm, and the other at 2ω, are combined to generate a sum‐frequency signal at 3ω from single asymmetric gold nanoantennas. This nonlinear signal interferes with the third‐harmonic radiation generated by the beam at ω, resulting in a modulation up to 50% of the total signal at 3ω depending on the relative phase between the beams. Such a large intensity modulation of the nonlinear signal is accompanied by a rotation of its polarization axis, due to the lack of central symmetry of the nanostructure. The demonstration that the nonlinear emission can be coherently controlled through the phase difference of the two‐color illumination represents a promising route toward all‐optical logic operations at the nanoscale through nonlinear optical signal manipulation. Abstract : An asymmetric plasmonic nanoantenna mediates the nonlinear mixing between ultrashort laser pulses at frequency ω and 2ω. Third harmonic at ω + ω + ω and sum frequency at ω + 2ω are coherent and degenerate in frequency at the visible frequency 3ω. Their interference depends on the temporal delay between pumps, enabling experimental coherent control of the nonlinear emission magnitude and polarization.